In‐depth proteomics approach of secretome to identify novel biomarker for sepsis in LPS‐stimulated endothelial cells. Issue 23 (13th September 2015) - Kwon, Oh Kwang; Lee, Wonhwa; Kim, Sun Ju; Lee, You‐Mie; Lee, Ju Yeon; Kim, Jin Young; Bae, Jong‐Sup; Lee, Sangkyu
Abstract : Sepsis and septic shock, which are conditions triggered by infection, occur with high incidence in emergency departments and are among the most common causes of death in hospitalized patients worldwide. Therefore, the identification of sepsis biomarkers for the rapid diagnosis is a major goal for researchers in the field of critical care. Endothelial cells play a pivotal role in orchestrating the inflammatory response triggered by sepsis. In this study, we used proteomics to investigate the secretome of EA.hy926 endothelial cells following lipopolysaccharide (LPS) stimulation with 1 μg/mL LPS for 12 or 24 h. SILAC in cell cultures and an online 2D‐LC‐MS/MS system were used to analyze the secretome dynamics in response to LPS. We found that 22 of the 77 secreted proteins identified in both the presence and absence of LPS and that 19 of the secreted proteins were quantified more strongly after LPS treatment for 24 h than after treatment for 12 h. By Gene Ontology and KEGG pathway analyses, we found that proteins related to the regulation of the actin cytoskeleton showed the highest secretion response to LPS stimulation. Out of the 19 candidate proteins, we focused on moesin, which is involved in the function of endothelial cells, and confirmed its amount in cellular lysates and media taken from primary human umbilical vein endothelial cells treated with LPS. To our knowledge, this study provides the first in‐depth analysis of the LPS‐induced secretome in human endothelial cells, and we propose 19 new biomarker candidates for sepsis, including moesin.